Multiple topologies from glycopolypeptide-dendron conjugate self-assembly: nanorods, micelles, and organogels - Pati, Debasis; Kalva, Nagendra; Das, Soumen; Kumaraswamy, Guruswamy; Sen Gupta, Sayam; Ambade, Ashootosh V. (Journal of the American Chemical Society, 2012)
Glycopolypeptides (GPs) were synthesized by ring-opening polymerization of glycosylated N-carboxyanhydride monomer and attached to hydrophobic dendrons at one chain end by ``click'' reaction to obtain amphiphilic anisotropic macromolecules. We show that by varying polypeptide chain length and dendron generation, an organogel was obtained in dimethylsulfoxide, while nanorods and micellar aggregates were observed in aqueous solutions. Assemblies in water were characterized by electron microscopy and dye encapsulation. Secondary structure of the GP chain was shown to affect the morphology, whereas the chain length of the poly(ethylene glycol) linker between the GP and dendron did not alter rod-like assemblies. Bioactive surface chemistry of these assemblies displaying carbohydrate groups was demonstrated by interaction of mannose-functionalized nanorods with ConA.

Effect of the branching pattern of hydrophobic dendrons on the core structure of linear-dendritic copolymer micelles - Kalva, Nagendra; Aswal, Vinod K.; Ambade, Ashootosh V. (Macromolecular Chemistry and Physics, 2014)
Hydrophobic dendrons based on different branching patterns, viz. 3,5-di- and 3,4,5-trisubstituted phenyl rings, consist of the same backbone but exhibit different sizes, shapes, and hydrophobic densities. These dendrons are attached to poly(ethylene glycol) and the core properties of the copolymer micelles are investigated in tetrahydrofuran (THF)/water mixtures by neutron scattering. Two polymers with intermediate hydrophobicity are studied further with variations in the solvent composition and the temperature. The aggregation numbers for 3,4,5-based dendron copolymers are lower, with more THF molecules of solvation compared with the 3,5-based dendron copolymer, the difference being greater at higher generations due to different molecular shapes. The micellar core size increases in small steps with dendron size so that dye encapsulation is tuned.
Keywords: diblock copolymers; linear-dendritic copolymers; micelles; neutron scattering; structure-property relations

Controlled micellar disassembly of photo- and pH-cleavable linear-dendritic block copolymers - Kalva, Nagendra; Parekh, Nimisha; Ambade, Ashootosh V. (Polymer Chemistry, 2015)
A linear-dendritic block copolymer with both photo-and pH-cleavable linkages at the junction between the hydrophobic dendron and hydrophilic linear polymer was synthesised. The photocleavable o-nitrobenzyl group attached to alkyne was introduced at the focal point of polyester dendron and acid-degradable acetal linkage with terminal azide was introduced at one end of linear polyethylene glycol. The two segments were connected using click chemistry. The copolymer was found to self-assemble into micelle-like aggregates in dilute aqueous solution. Stimuli-responsive disassembly of the aggregates was studied by monitoring fluorescence emission of the encapsulated hydrophobic dye and dynamic light scattering (DLS). Products of acetal cleavage at acidic pH were analyzed by gel permeation chromatography and NMR spectroscopy. The photo and pH stimuli were applied separately as well as simultaneously to study the rate of dye release. The synergistic effect of the two stimuli on dye release was demonstrated and the non-cytotoxic nature of the polymer was shown using the MTT assay. Cell uptake of DOX-loaded micelles and photo-induced release of the drug resulting in significantly higher cytotoxicity than by free DOX was demonstrated using MDA-MB-231 cells.

Photoresponsive assemblies of linear-dendritic copolymers containing azobenzene in the dendron interior: the effect of the dendron structure on dye encapsulation and release - Kalva, Nagendra; Basutkar, Nitin B.; Ambade, Ashootosh V. (RSC Advances, 2016)
Hydrophobic dendrons with different numbers and positions of azobenzenes as well as different groups benzyl and dodecyl, on the periphery were synthesised and attached to poly(ethylene glycol) using copper-catalysed azide-alkyne cycloaddition to obtain linear-dendritic copolymers. Self-assembly of the polymers in aqueous solution was characterised using dynamic light scattering (DLS), transmission electron microscopy (TEM) and critical micelle concentration (cmc). Formation of H-aggregates during micellisation was shown for polymers with a higher number of azobenzene units. Photoisomerisation of azobenzene in the assemblies was studied and the rate constant of thermal photoisomerisation was calculated. Release of hydrophobic dye Nile red upon photoisomerisation of azobenzene occurred without disruption of micellar aggregates. Dye release varied with the pathway - thermal or visible light irradiation, followed for cis-trans isomerisation. The encapsulation capacity of the micelles and extent of dye release in either pathway were found to be influenced by the dendron structure. A polymer with a lower number of azobenzenes and aliphatic periphery on the dendron showed significantly different behaviour than polymers with a larger number of aromatic units.

Synthesis and tunable thermoresponsive solution morphologies of 2,2-bis-methylolpropionic acid dendron-azobenzene-poly(N-isopropyl acrylamide) copolymers - Kalva, Nagendra; Ambade, Ashootosh V. (Polymer International, 2017)
Amphiphilic temperature- and photoresponsive linear-dendritic block copolymers comprising second-generation acetonide-2,2-bis-methylolpropionic acid-based polyester dendron and linear poly(N-isopropyl acrylamide) (PNIPAM) linked by an azobenzene unit were synthesized using atom transfer radical polymerization (ATRP) followed by click chemistry. Linear PNIPAM precursor was prepared from an azide-functionalized azobenzene containing ATRP initiator. Two polymers obtained by varying the chain length of the PNIPAM block showed different morphologies and lower critical solution temperature (LCST) values in aqueous solution. Complete change in morphology of the two polymers into large spherical aggregates and nanotubes, respectively, was observed upon heating the micellar solution above LCST. The azobenzene unit was found to undergo trans-cis photoisomerization in the assemblies and caused a change in the microenvironment of an encapsulated hydrophobic dye without any release. Acetonide groups on the dendron were deprotected to afford hydroxylated polymer that showed well-defined morphologies above the LCST and after heating-cooling cycle while significant dye encapsulation was seen only above the LCST. (c) 2017 Society of Chemical Industry